Donald C. Haggis and Carla M. Antonaccio (eds). Classical Archaeology in Context: Theory and Practice in Excavation in the Greek World. - Gaignerot-Driessen, Florence (Journal of Greek Archaeology, 2017)
This volume is a collective, multi-regional, multi-period, and multi-disciplinary reflexion on what is and what should be classical archaeology. The 13 contributions collected are organised in four chapters, respectively paying attention to ‘historical contexts and intellectual traditions’, ‘mortuary’, ‘urban and rural’, and ‘sanctuary contexts’. The study cases presented come from Crete (Praisos, Azoria, and Arkalochori), Rhodes (Kymissaleis), Lycia (Çaltılar Höyük), Macedonia (Platania, Kompoloi, Douvari, Krania, and Vergina), the Peloponnese (Argos, Elis, Megalopolis and the island of Poros), Attica (Athens, Vourva, Marathon), and Sicily (Morgantina). The papers consider archaeological contexts dated from the Geometric to the Hellenistic period. A wide range of archaeological specializations, such as ceramology or bioarcheology (paleobotany, archeozoology, physical anthropology), and technologies (photogrammetry, interrelational database, tomography, geophysical survey, INAA, petrography, pXRF), is represented and discussed by the different contributors.